Gambaran Pola Tidur Ibu Hamil Di Rumah Sakit X Jakarta Utara - Esti Winarni; Ricky Riyanto Iksan; Roza Indrayeni (Akademi Keperawatan Yarsi Samarinda, 2026)
Sleep patterns are a crucial basic need during pregnancy because they impact the physical and psychological well-being of pregnant women. This study aims to describe the sleep patterns of pregnant women at Hospital X, North Jakarta. This study employed a quantitative descriptive approach with a univariate data analysis approach. The sample size was 70 respondents. Results: Based on the results, 35.7% of respondents reported good sleep quality with a PSQI score ≤ 5, indicating that approximately one-third did not experience significant sleep disturbances. Furthermore, 35.7% of respondents reported mild sleep disturbances, making the proportion similar to that of the group with good sleep quality. Meanwhile, 28.6% of respondents reported moderate sleep disturbances, indicating that nearly one-third were beginning to experience significant sleep problems. This study found no respondents with severe sleep disturbances (0%). Conclusion: The majority of respondents reported good to mild sleep disturbances. However, a significant number of respondents reported moderate sleep disturbances (28.6%), suggesting that sleep quality still warrants attention. The absence of severe sleep disturbances indicates that the level of sleep disturbance in this group is not yet severe.